Regenerative endodontic treatment of an immature permanent canine - A case report of a 13-year follow-up - Roy Petel; Avia Fux Noy (Wolters Kluwer Medknow Publications, 2021)
Data on long term survival and tooth stability after regenerative endodontic treatment are missing. The purpose of the present report is to describe regenerative endodontic treatment of a permanent mandibular canine with extensive coronal hypoplasia, immature root, and a periapical radiolucency. The regenerative endodontic treatment was initiated by irrigation of the root canal, followed by three weeks of triple antibiotic paste dressing and the creation of a blood clot scaffold covered with mineral trioxide aggregate. A one year clinical and radiographic follow-up demonstrated healing of the periapical radiolucency and the tooth remained stable and sound for almost thirteen years post treatment.